Analisis rencana pelaksanaan pembelajaran kelas V tema 1 menurut kurikulum 2013 - Gabriella Sihnanda Ajeng Widyaningrum; Jenny Indrastoeti Siti Poerwanti; Matsuri Matsuri (Universitas Sebelas Maret, 2021)
This research aims to analyze the suitability of the components of the lesson plan of fifth grade theme 1 according to 2013 curriculum. This research used descriptive qualitative research method. As a data collection technique, the writer used documentation technique. As a data analyze, the writer used descriptive qualitative technique. The results showed that the lesson plan of grade V theme 1, component the identity of the lesson, lesson purpose, media, study materials, opening activity, main activity, closing activity, and assessment are suit according to 2013 curriculum. The results of this research indicate that the lesson plan of fifth grade Theme 1 that made by the teacher is in accordance with the provisions of the 2013 curriculum in terms of the components of lesson plan identity, learning objectives, learning media, teaching materials, opening activities, core activities, closing activities, and assessment. The implementation of the lesson plan will be maximized if the preparation pays more attention to the principles and criteria for the preparation of an appropriate lesson plan according to the 2013 curriculum. This research can practically be used as a reference material for teachers and schools in preparing an appropriate lesson plan according to the 2013 curriculum.